TREATMENT OF ACUTE INFLAMMATORY DISEASES ACCOMPANIED BY THROAT IRRITATION AND PAIN - M. I. Petrovskaya (Union of pediatricians of Russia, 2013)
Pathogenetically, prescription of local action drugs containing a wide spectrum antiseptic is reasonable for the upper respiratory tract diseases accompanied by throat irritation and pain. It should be noted that such drugs are very popular among parents; however, most of these drugs may have a range of side effects, which considerably complicate their use in children. That is why the right choice of local action drugs for the acute inflammatory diseases accompanied by throat irritation and pain is a guarantee of treatment efficacy and high compliance. This article examines pharmacological qualities of an antiseptic-containing local action drug permitted to use in children over 4 years of age.